U.S. States’ fiscal constraints and effects on budget policies - Iannella Mario (Perspectives on Federalism, 2016)
The article looks at fiscal constraints adopted by the U.S. States. It questions the ability of those rules to determine sound budgetary policies. To assess this point it analyses, in the general part, the major kind of constraints so far adopted. Of each major category the focus is upon institutional weaknesses that create the room for the adoption of circumventing practices. The following section focuses instead on three case studies, to show examples of the way in which the constraints influenced policy-making without mining the ability of government to adopt unbalanced budgetary policies. The weaknesses are combined with the adoption of a deferential approach by the Courts that generally legitimized the accounting devices adopted by the States. The outcome is a system in which budget policies are influenced by several factors that go beyond the institutional framework. On the other side, legal boundaries create distortions and unwanted effects in policies implemented by the States.